PENGUATAN KINERJA SDM MELALUI TEKNOLOGI INFORMASI PADA UMKM - Kusumawati, Diah Ayu; Nurcahyo, Satria Avianda (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
Intense competition makes companies have to be able to compete in the global industry. Improving the quality of human resource performance has an important role in improving the quality of the company. Various factors can support HR performance such as self-competence, Islamic work ethics and information technology. Someone who has self-competence and a good Islamic work ethic can improve the performance of his human resources. Support from information technology expertise can also strengthen the relationship between self-competence and Islamic work ethics in improving HR performance. This study uses SPSS 16 testing. The results of this test show that self-competence and Islamic work ethic can affect HR performance. Meanwhile, information technology cannot be a moderator and does not strengthen the relationship between self-competence and Islamic work ethics on HR performance in MSMEs in Central Java. This means that information technology in MSMEs has been widely used, but its use is not optimal and so it is not able to support improving the performance of its human resources